The spatiotemporal distribution characteristics and influencing factors of ancient tombs in China: A study on the conservation of ancient tombs in China - Quanbao Ma; Yujia Li; Zhen Yang; Xing Zhao; Can Li; Zi Shi; Zimu Li (PLoS ONE, 2025)
Ancient tombs were valuable cultural heritage of China and possessed immeasurable significance. However, research on their spatiotemporal distribution and influencing factors was relatively absent. Based on the establishment of a national geographic information database of ancient tombs, this study employed ArcGIS and SPSS software to conduct both qualitative and quantitative analyses of the extant ancient tombs in China, with the aim of providing support for the protection of Chinese ancient tombs. The results showed that: ① The number of ancient tombs in the Qing Dynasty was the highest, while the number of ancient tombs from the Sui Dynasty accounted for the smallest proportion; ② Ancient tombs in different historical periods presented three distinct concentration areas around the Central Plains urban agglomeration, Chengdu-Chongqing urban agglomeration, and Guanzhong Plain urban agglomeration in China; ③ The focus of ancient tombs in different historical periods concentrated in the central region of China, with a recurring shift of the focus within the current provinces of Shaanxi, Shanxi, Henan, Hubei, and Chongqing; ④ The density of southern rice paddies (DL01) was negatively correlated with the distribution of ancient tombs in China, while the total GDP and population had a significant positive correlation with the distribution of ancient tombs. The significance of this study lies in systematically understanding the spatiotemporal distribution patterns and influencing factors of ancient tombs in China, in order to provide a theoretical basis for scientifically assessing risks, formulating effective protection plans, and guiding archaeological surveys and explorations.